'Source Silver': An Informant, Collaboration and the Ambiguity of an Indian Socialist Ideal. Issue 4 (2nd October 2017) - Kuracina, William F.
ABSTRACT: This paper examines Indian socialist ideals that transcended India's Independence in 1947. It introduces a Delhi Police Special Branch confidential informant, 'Source Silver', who monitored socialist activities in 1946 and 1947—a peculiar situation in which the conduct of socialist Congressmen was scrutinised by Congressmen in office. The essay also highlights the precise continuity of socialist ideals which originated within the first few years of the Congress Socialist Party's founding and continued after Independence. Likewise, it suggests that these ideals proved ill-suited to the Interim Government period from September 1946 up to the eventual transfer of power in August 1947, a misalignment which prompted Congress socialists to separate from, or have their separation engineered by, the Indian National Congress in early 1948.